Особливості фізичної активності чоловіків зрілого віку - Пришва, Олесь; Prishva, Oles (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті досліджено особливості фізичної активності чоловіків зрілого віку 22–50 років (n =101 ) – військовослужбовців. Обраховано показники МЕТ (metabolic equivalent of task) для трьох вікових категорій чоловіків зрілого віку. Визначено відсоткові тенденції фізичної активності в трьох зонах інтенсивності. Проаналізовано відсотки кількості занять на тиждень відповідно до зон інтенсивності та вікових категорій. Research purpose is to define the features of physical activity of men of mature age on the improved methods of international questionnaire IPAQ. In the article the features of physical activity of military men of the age of18-50 years (n = 101) were examined . The metrics MET (metabolic equivalent of task) for three age categories of men of mature age were calculated. The percentage trends of physical activity in three areas of intensity are identified. Percentage of number of classes per week according to the zones of intensity and age categories are analyzed.
Features of Physical Activity of Men of Mature Age
Keywords: чоловіки зрілого віку; фізична активність; IPAQ; MET; men of mature age; physical activity; the IPAQ; the MET